Evaluation of nutritional status in non-small-cell lung cancer: screening, assessment and correlation with treatment outcome. Issue 3 (17th May 2020) - Trestini, Ilaria; Sperduti, Isabella; Sposito, Marco; Kadrija, Dzenete; Drudi, Alessandro; Avancini, Alice; Tregnago, Daniela; Carbognin, Luisa; Bovo, Chiara; Santo, Antonio; Lanza, Massimo; D'Onofrio, Mirko; et al.
Abstract : Background Nutritional derangements are common hallmarks of non-small-cell lung cancer (NSCLC). Nevertheless, their early detection is overlooked in clinical routine. This study aimed to evaluate nutritional status and its correlation with outcome in NSCLC patients. Methods Data regarding NSCLC patients undergoing nutritional evaluation were prospectively collected (May 2016–October 2018). Nutritional risk was assessed by Nutritional Risk Screening 2002 (NRS-2002). Bilateral psoas major muscles were measured at L3 vertebrae level with routine staging-computed tomography and changes were evaluated using Wilcoxon signed-rank test. Clinico-pathological and nutritional data were correlated to progression-free/overall survival (PFS/OS) and response rate (ORR) using a Cox and logistic regression model. Kaplan–Meier curves were compared with log-rank test. Results Thirty-eight patients were included. The majority (65.8%) of them were at nutritional risk (NRS-2002 ≥3). At multivariate analysis for patients with advanced disease, age (HR 2.44, p=0.05), performance status (HR 2.48, p=0.043) and NRS-2002 (HR 1.74, p=0.001) were significant independent predictors for PFS and weight loss (HR 1.07, p=0.008) for OS. Patients with baseline NRS-2002 <3 had significantly longer 1-year PFS (85.7% vs 19.4%, p=0.02) and higher ORR (66.7% vs 21.4%) than those with NRS-2002 ≥3. An explorative evaluation demonstrated that NRS-2002 score significantly decreased after nutritional intervention (p=0.001) for 3 months. Conclusion Baseline nutritional risk represents a prognostic factor in NSCLC. Nutritional counselling should be applied as a fundamental tool to improve nutritional risk in a short period, ameliorating patients' outcome.